Industry 4.0: The New Quality Management Paradigm in Era of Industrial Internet of Things - DurakoviÄ‡, Benjamin; Halilovic, Maida (JOIV : International Journal on Informatics Visualization, 2023)
Advanced technologies such as Big Data, the Internet of Things, artificial intelligence, robotics, cloud computing, and additive manufacturing are enablers of the industry 4.0 revolution and signify intense transformations in socio-economic systems. This work investigates the enabling nature of certain technologies in the emergence and development of different quality paradigms. Each enabling technology is related to a certain industrial revolution; consequently, a certain quality paradigm has been developed. Where is quality management now, in which direction its development is going, and what can be expected in the future is discussed in this paper. The research focuses on the most important factors discussed in the literature that influenced quality development throughout history. Results are presented in written and graphical form and include newly established theories based on recent innovations. Since this is a cumulative overview of different quality methods, it only briefly discusses the most important theories. It was observed that with Industry 4.0 enabling technologies, we are currently experiencing a transformation in this discipline, reaching a higher level in the competition for market positioning. Particularly, meeting explicit customer needs is upgraded with latent customer needs - linked to the customer's emotional responses (delight) to products/services. This paper contributes to a new field of research that is becoming increasingly popular.